The specialist nursing workforce caring for men with prostate cancer in the UK. Issue 1 (17th November 2015) - Leary, Alison; Brocksom, Jane; Endacott, Ruth; Fleure, Louisa; Howdle, Felicity; Masterton, Morven; O'Connor, Anita; Swift, Adrian; Trevatt, Paul; Aslet, Philippa
ABSTRACT: Prostate cancer is the most common cancer in men in the UK accounting for 25% of all new cases of cancer. It is predicted to become the most common cancer overall by 2030. A national survey of the specialist nursing workforce caring for men with prostate cancer was completed across the four countries of the UK during June and July 2014. In total 302 specialist nurses completed the survey and data from 285 was used in the analysis. This is the biggest whole population survey of this workforce in recent years. The most common job title was clinical nurse specialist (185) and the most common band was agenda for change band 7 (174). However in Scotland 50% of the respondents stated that they were paid on band 6. Over half the group (158) had worked in prostate cancer care for more than 10 years. Few (48) had come into specialist posts from a specific specialist nurse development role. There is wide geographic variation in the provision of specialist nursing for men with prostate cancer. This is reflected in available hours and caseload sizes. The respondents reported frozen and vacant posts across the UK. This equated to 58·3 full time equivalents. The work of specialist nurses caring for men with prostate cancer is clinically complex and appears to cover most key times in the cancer journey. However workload appears to be limiting the care that the nurses are able to provide with over half the respondents (163) saying that they left work undone for patients.